Optimization of KOH Catalyst Concentration and Reaction Temperature for Biodiesel Production from Waste Cooking Oil - Achmad Aminudin; Bintang Arisendy; Agus Choirul Arifin; Nur Ihda Farikhatin Nisa (Department of Chemistr Education Faculty of Teacher Training and Education Universitas Su, 2026)
This study aims to analyze the effects of variations in the KOH catalyst concentration and reaction temperature on the yield and characteristics of biodiesel produced from waste cooking oil through a transesterification process. The KOH catalyst concentration was varied at 0.5%, 1%, and 1.5%, while the reaction temperatures were set at 60°C, 65°C, and 70°C, respectively. The oil-to-ethanol molar ratio was maintained at 1:6, with a reaction time of 90 minutes and a stirring speed of 500 rpm. The results show that both the catalyst concentration and the reaction temperature influence the biodiesel yield and physical properties, including the density, viscosity, flash point, and calorific value. The highest biodiesel yield of 93.36% was achieved at a KOH concentration of 1% and a reaction temperature of 65°C. The biodiesel density ranged from 844.7 to 870.2 kg/m³, meeting the SNI 7182:2024 standard. The lowest viscosity, 4.78 cSt, was obtained at KOH concentrations of 1.5% and 70°C and remained within the acceptable standard range. All the samples exhibited flash points above 153.5°C. The highest calorific value, 49,682 J/g, was recorded at a KOH concentration of 1.5% and a reaction temperature of 70°C. Overall, the optimal conditions for maximum yield were 1% KOH and 65°C, whereas a higher reaction temperature of 70°C enhanced the energy quality of the biodiesel.